A Comparative Study of Autologous and Acellular Dermal Matrix Static Cheek Slings in Corrective Surgery for Facial Palsy. Issue 6 (December 2021) - Cabañas Weisz, Laura M.; Guarin, Diego L.; Townley, William A.
Abstract : Background: Facial palsy causes devastating disability due to loss of facial function as well as social and psychological impairment. Cheek slings are a secondary technique that provide static support to the midface. This study aimed to describe our technique and compare a traditional sling material (tensor fascia lata) with a porcine-derived acellular dermal matrix alternative (Strattice). Methods: A 5-year case-control retrospective review of consecutive static cheek slings in a tertiary cancer and facial palsy center was performed. Demographic data, risk factors, and complications were collected and compared. Improvement in static smile position was assessed by Emotrics (Massachusetts Eye and Ear Infirmary, Boston, MA) at 3 months. Long-term sling failure was assessed by need for reoperation. Results: The study group comprised 41 patients on which 33 autogenous fascia lata slings and 12 Strattice slings were performed. Medium-term improvement in static smile position was similar between the 2 groups (judged by the Emotrics software), as was complication rate ( P = 0.496). Need for revision due to stretching was higher in the Strattice group but did not achieve significance ( P = 0.087). Mean follow-up was 38.02 ± 19.17 months. Twelve of 41 patients were deceased at study conclusion. Conclusions: Fascia lata and Strattice slings provide satisfactory results in restoring symmetry at rest and functional oral competence. Our results suggest that Strattice is a safe sling material with an acceptable risk profile and comparable medium-term maintenance of tensile strength to fascia lata, and should be considered where life expectancy, donor site morbidity, and procedure length are important considerations.